The structure and origin of loess dolls: a case study from the loess-paleosoil sequence of Süttő, Hungary - Barta, Gabriella (Journal of Environmental Geography, 2011)
The research of secondary carbonates from loess-paleosoil sequences focuses not just on the micro-scale types, but as well on the macro-scale ones. Loess dolls or concretions belong to this last category. Concretions are found frequently under the paleosoil levels referring to a very probable connection with leaching processes and precipitation from carbonate-rich solutions. Research was carried out on the loess-paleosoil sequence of Sütto", Hungary. The methods used in this work were the morphological description of concretions, the analysis of the structure after cutting into two or more parts and treatment with 10% hydrochloric acid. Altogether 29 samples were analysed from the sandy loess layers between the depth of 0.65–5.55 m and 12.70–14.75 m. Based on the results three main types concerning the inner structure of the concretions were determined: a.) concretions with longitudinal and/or perpendicular cracks; b.) concretions containing one or more condensation nucleus; c.) the combination of the above listed proper-ties. From these different structures more conclusions could be drawn on the origin of loess dolls. The carbonate precipitation could have taken place in or around cavity systems of biogenic origin (as root-related channels or features, and biogalleries) and of non-biogenic origin (because of the structural properties of the sediment). As precipi-tation nuclei the cementation of hypocoatings played an important role as well. A multiphase development history of the loess dolls were in many cases characteristic.